Effects of Using Student Worksheets Integrated With Context-Based Learning Videos on Collaboration and Science Communication Skills Students - febrianti, kurnia; Desnita, Desnita (Journal of Innovative Physics Teaching, 2024)
Collaboration and science communication are skills that are needed and must be possessed by students. In reality, students are less trained to work together and express ideas well, so students' science collaboration and communication skills are still weak. Therefore, student worksheets integrated with context-based learning videos are used as a solution. This study aims to see the influence of using student worksheets integrated with context-based learning videos on improving students' collaboration skills and science communication skills. Students of class XI IPA 3 at SMAN 3 Payakumbuh were used as the research sample. The instruments used were observation sheets on collaboration and science communication skills. The results of the data analysis showed: 1) there was an increase in students' collaboration skills score from 40.29 to 85.59 with an excellent category, and 2) there was an increase in students' science communication skills score from 40.29 to 76.91 with a good category. Based on the t-test conducted, there is a positive effect of using student worksheets integrated with context-based learning videos on students' collaboration and science communication skills.